2000
DOI: 10.1007/pl00008337
|View full text |Cite
|
Sign up to set email alerts
|

Snoring, noisy breathing in sleep and daytime behaviour in 2–4-month-old infants

Abstract: Snoring and noisy breathing during sleep, rather common symptoms in young infants, may be associated with specific behavioural disturbances, and moody infants should be investigated carefully for possible obscure respiratory problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
3
18
2
Order By: Relevance
“…More infants aged 2–3 months were reported to habitually snore than younger infants. In another community sample of infants, mothers reported habitual snoring in 5% of infants, noisy breathing other than snoring in 24%, and snoring and noisy breathing in 6.5% of infants aged 2–4 months 42. In the present study, there were no significant differences between snoring and non-snoring infants with respect to infant or maternal characteristics, including feeding and maternal smoking.…”
Section: Discussioncontrasting
confidence: 66%
“…More infants aged 2–3 months were reported to habitually snore than younger infants. In another community sample of infants, mothers reported habitual snoring in 5% of infants, noisy breathing other than snoring in 24%, and snoring and noisy breathing in 6.5% of infants aged 2–4 months 42. In the present study, there were no significant differences between snoring and non-snoring infants with respect to infant or maternal characteristics, including feeding and maternal smoking.…”
Section: Discussioncontrasting
confidence: 66%
“…Infants with prolonged apnea may also have increased lethargy, abnormal spontaneous movements, feeding difficulty, failure to thrive, and developmental delay [11,18]. It has been shown that failure to thrive could be reversible in some infants with LM, and limited studies suggest that neurocognitive and behavioral sequelae may be at least partially reversible [18].…”
Section: Discussionmentioning
confidence: 97%
“…Indications for surgery in this group can be more ambiguous, and PSG may play an important role in the decision making process for some of these patients [3]. While the accuracy of subjective caregiver reports and clinical assessment by physicians in predicting sleep apnea in children is unclear [11,12], PSG is an effective ''gold standard'' in identifying and quantifying sleep apnea and may provide valuable information in the workup of infants with moderate LM [2,13]. In this study, nine children with a non-severe LM were found to have moderate or severe OSA and subsequently underwent a SGP.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…16 Prevalence rates of snoring similar to those of preschool-and early school-aged children have been reported among infants. Indeed, habitual snoring was found in 5% of 2-to 4-month-olds 30 and in 6-to 12-month-olds, 26 with higher rates in infants who are aged 1 to 8 months (16 -26%). 31 More recently, we found habitual snoring in 1% to 9% of infants and toddlers (2-24 months of age).…”
mentioning
confidence: 99%